(untitled) (Journal of Comparative Social Work, 2010)
This article investigates the sources of job satisfaction among practitioners and managers employed in the Norwegian public social services and the professionals´ perception of social rewards in particular. Being valued, receiving praise and positive feedback are considered to be important aspects of job satisfaction. Nevertheless the expertise and competence of social workers is not always acknowledged. A central question raised is whether the workers´ job satisfaction is influenced by their opportunities for support and recognition, compared to other (intrinsic and organisational) rewarding aspects available to social service workers. The empirical data come from a 2004 quantitative survey among social workers in local welfare agencies. Despite conflicting demands and lack of resources in the front line services, findings indicate that managers and practitioners perceive their work as overall equally satisfying. Still, the managers find their job more interesting and challenging due to their position, reporting higher feelings of accomplishment and control over work. Receiving public approval and co-worker support are positively associated with job satisfaction within both work positions, while superior support and client recognition were found to be significantly rewarding aspects to the practitioners only. The final discussion addresses the challenges for an organizational climate that sustain the worth and contribution of social professionals